Sister outsider : essais et propos d'Audre Lorde sur la poésie, l'érotisme, le racisme, le sexisme... - Lorde, Audre (Mamamélis, 2003)
Ensemble de textes de la poétesse et militante féministe noire américaine (1934-1992) où elle exprime sa pensée sur les injustices civiles et sociales, les droits civiques, le féminisme, l'identité féminine noire. Un souvenir revient dans les écrits d'Audre Lorde. C'est l'hiver à New York. Audre est dans le métro avec sa mère. Emmitouflée, elle est assise à côté d'une dame en manteau de fourrure. Elle regarde la dame, blanche, qui d'une main rageuse retire le pan de manteau qui effleure l'enfant. Une enfant Noire qui ne comprend pas et cherche désespérément un cafard, une poussière, bref une saleté justifiant ce geste. Quelque chose pour ne pas réaliser que la saleté... c'est elle. Ensuite, le regard rageur de la dame blanche qui tue l'enfant Noire de cinq ans parce qu'elle ne peut pas le nommer : le regard du racisme. Un souvenir vrillé en elle, plus qu'une douleur, une souffrance indélébile qui permet à la poète adulte d'affirmer qu'au fond, en Amérique, on ne veut pas que les Noir-e-s vivent. Audre a vécu, survécu, pour nous dire son « amérique », ses passions, ses colères, dans une série d'écrits lumineux.
Donné en lecture cours FEM1000:"Âge, race, classe sociale et sexe: les femmes repensent la notion de différence" p.125-136 "De l'usage de la colère: la réponse des femmes au racisme" p.137-148
Keywords: 1900-1999; afro-féminisme; amériques; antiracisme; approches et analyses; arts; care; cours; cycles supérieurs; discipline; fem1000; fem3100; fem7000; féminismes noirs; incontournable; lesbianisme; lit3220; littérature; militance; premier cycle; périodes historiques; régions géographiques; thématiques; violences; émotions; états-unis; études littéraires

Women making art: history, subjectivity, aesthetics - Meskimmon, Marsha.. (Routledge, 2003)
Women have been making art for centuries, yet their work has been seen as secondary or has gone unrecognized altogether. "Women making art" asks why this is so, and what it would take for us to realize the extent of women's extraordinary contribution to the arts. Marsha Meskimmon mobilizes contemporary feminist thinking to reconsider how and why women have made art. She examines work by a wide range of women artists fomr different cultures and historical periods, including Rebecca Horn, Rachel Whiteread, Shirin Neshat and Maya Lin, emphasizing the diversity of women's arts and the importance of differences between women.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires

Veil: veiling, representation, and contemporary art - Tawadros, Gilane; Bailey, David A. (MIT Press ; IVA, 2003)
No single item of clothing has had greater influence on Western images of Middle Eastern and North African women than the veil. The fascination of Western writers, artists, and photographers with the veil reflects the voyeuristic nature of our interest in what is strange and "other." Veil, which accompanies an exhibition organized by the Institute of International Visual Arts in London, explores the representation of the veil in contemporary visual arts. Providing a context for the commissioned essays are a number of classical historical texts crossing religions, cultures, genders, and ages–from Greek myths to articles published in the aftermath of September 11, 2001. Some of the contemporary artists and scholars write autobiographically about the meaning of the veil in their lives. Others take a more political approach, discussing, for example, how the events of September 11 changed the use and reception of veil imagery throughout the world. Still others take a historical approach, examining how nineteenth-century technological developments in travel and photography led to photographic depictions of both the veiled and unveiled body in relation to landscape. A number of essays look at the art historical precedents for the current interest in artwork addressing the veil, while others examine how codes of modesty and gender segregation have affected the making and viewing of films in postrevolutionary Iran. The essays are by Jananne Al-Ani, David A. Bailey, Alison Donnell, Ghazel, Salah Hassan, Reina Lewis, Hamid Naficy, Zineb Sedira, and Gilane Tawadros. The artists represented include Faisal Abdu'Allah, Kourosh Adim, Ghada Amer, Jananne Al-Ani, Farah Bajull, Samta Benyahia, Gaëtan de Clérambault, Marc Garanger, Shadafarin Ghadirian, Group AES, Emily Jacir, Ramesh Kalkur, Shirin Neshat, Harold Offeh, Gillo Pontecorvo, Zineb Sedira, Mitra Tabrizian, and Elin Strand.
Section: 187 p. : illustrations en noir et en coul. ; 22 cm
Keywords: afrique; afrique du nord; approches et analyses; arts; corps; cours; discipline; féminisme islamique; har4610; histoire de l'art; mode; moyen-orient; point de vue situé; premier cycle; régions géographiques; thématiques; vêtements